Case study on a scientific oral history project using information practice analysis - Deborah A. Garwood (Information Research: An International Electronic Journal)
Introduction. This investigation explored 21st century stewardship of a late 20th century scientific oral history project through the lens of information practice. Oral history project stewardship and reuse are understudied.